2020
DOI: 10.1016/j.cub.2020.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Planar Bipolarity Emerges from Notch-Mediated Asymmetric Inhibition of Emx2

Abstract: Most plane-polarized tissues are formed by identically oriented cells [1,2]. A notable exception occurs in the vertebrate vestibular system and lateral-line neuromasts, where mechanosensory hair cells orient along a single axis but in opposite directions to generate bipolar epithelia [3][4][5]. In zebrafish neuromasts, pairs of hair cells arise from the division of a non-sensory progenitor [6, 7] and acquire opposing planar polarity via the asymmetric expression of the polarity-determinant transcription factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 61 publications
1
49
0
Order By: Relevance
“…Consistent with the DPT analysis, the nascent HC cluster showed significantly higher number of emx2 read-counts ( Figure 3E) and percentages of emx2-positive cells ( Figure 3F) than other clusters. Taken together, our scRNA-seq results showed that, similar to previous results (Kozak et al, 2020), emx2 transcripts were found within the HC lineage except we found that the transcripts initiate as HCs transitioned from precursors to nascent HCs rather than peaking early in the precursor cell population as described previously (Kozak et al, 2020). The difference between these results is not clear and may be attributed to the difference in the age of the larvae and the number of HCs analyzed.…”
Section: Results Emx2 Transcription Initiates During Precursor To Dausupporting
confidence: 86%
See 4 more Smart Citations
“…Consistent with the DPT analysis, the nascent HC cluster showed significantly higher number of emx2 read-counts ( Figure 3E) and percentages of emx2-positive cells ( Figure 3F) than other clusters. Taken together, our scRNA-seq results showed that, similar to previous results (Kozak et al, 2020), emx2 transcripts were found within the HC lineage except we found that the transcripts initiate as HCs transitioned from precursors to nascent HCs rather than peaking early in the precursor cell population as described previously (Kozak et al, 2020). The difference between these results is not clear and may be attributed to the difference in the age of the larvae and the number of HCs analyzed.…”
Section: Results Emx2 Transcription Initiates During Precursor To Dausupporting
confidence: 86%
“…However, immunostaining may not be sensitive enough to detect onset of emx2 transcription. Indeed, a recent study demonstrated enriched Emx2 transcripts and immunoreactivity in HC precursors using immunostaining, in situ hybridization and scRNA-seq (Kozak et al, 2020). These results imply that the downregulation of Emx2 in one of the nascent HCs generated the asymmetry within a pair of HCs ( Figure 1C).…”
Section: Results Emx2 Transcription Initiates During Precursor To Daumentioning
confidence: 58%
See 3 more Smart Citations